2002
DOI: 10.1074/jbc.m202248200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-scanning Mutagenesis Reveals a Conformationally Sensitive Reentrant Pore-Loop in the Glutamate Transporter GLT-1

Abstract: Removal of glutamate from the synaptic cleft by (Na ؉ ؉ K ؉ )-coupled transporters prevents neurotoxicity due to elevated concentrations of the transmitter. These transporters exhibit an unusual topology, including two reentrant loops. Reentrant loop II plays a pivotal role in coupling ion and glutamate fluxes. Here we used cysteine-scanning mutagenesis of the GLT-1 transporter to test the idea that this loop undergoes conformational changes following sodium and substrate binding. 15 of 22 consecutive single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
0
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 43 publications
(59 reference statements)
8
51
0
3
Order By: Relevance
“…10A) and 449 (Fig. 3B) and also at position 443 (36). These observations are in harmony with the TBOA-bound Glt Ph structure, which represents an "open" conformation where HP2 has moved toward (36), 448, and 449 and presumably also the intervening residues, although the latter could not be tested because the lack of activity of the cysteine mutants at positions 444 -447 (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…10A) and 449 (Fig. 3B) and also at position 443 (36). These observations are in harmony with the TBOA-bound Glt Ph structure, which represents an "open" conformation where HP2 has moved toward (36), 448, and 449 and presumably also the intervening residues, although the latter could not be tested because the lack of activity of the cysteine mutants at positions 444 -447 (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…3B, 5B, and 10 and Ref. 36), render the explanation of an overall a physical blockade of external accessibility of HP2 highly unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30). However, recently more and more examples (36,54) of residues in loops were found that, similar to E252C in NhaA, affect the kinetics and other parameters of the transporters. It is clear that atomic resolution of NhaA as of the other transporters is needed to get a glimpse as to how and, whether directly or indirectly, loops participate in the translocation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Pore-loop structures are loop regions that fold back between the TMSs and are commonly observed in channel proteins where they function as selectivity filters (23,24). Well studied examples are the bacterial and neuronal glutamate transporters, GltT and GLT-1, in which pore-loops were shown to play an important role in the translocation event (17,18,25,26). Pore-loop structures are not observed in the LacY and GlpT structures, and it is unknown whether or not they represent a different translocation mechanism.…”
mentioning
confidence: 99%